Let us assume salaries are j & k and increased ones are j+jp/100 and k+kp/100

So new salaries are say j2 & k2.

We now have two equations.

j2 = j+ jp/100

k2 = k + kp/100

Statement 1) k - j = 2000. Not Sufficient to calculate.

Statement 2) k2 - j2 = 2440. Not Sufficient to calculate.

Let us combine to the two statements :

k2 - j2 = 2440 = k+ kp/100 - ( j + jp/100)

=> ( 1 + p/100)( k - j )

=> ( 1+ p/100) * 2000

=> This is sufficient to calculate p.

## Please log in or register to add a comment.